PENDEKATAN OBJEKTIF: KARYA SASTRA PUISI “PENERIMAAN” KARYA CHAIRIL ANWAR - Demylia Lady Amara; Salsabella Wawa Anasya; Nur Halimatusyadiyah Nur Halimatusyadiyah (Universitas Batanghari, 2022)
Literary works are literary, written works that, compared to other writings, have various advantages, such as authenticity, artistry, beauty in their content and expression, drama, epic, and lyrics. A literary work in poetry is an overflow of expression of an emotional soul. Poetry is categorized as a unique literary work because it is created from imagination and contains the most profound experiences of its poets analogous to beautiful language. A poem is a literary work with a language that is compacted, shortened, and rhythmically given with a solid sound and a selection of figurative (imaginative) words. It serves as a means by which man expresses and expresses his thoughts and feelings to other human beings. An objective approach is an approach that orients or focuses attention on the poem itself. Poetry is considered an object of self-sufficiency, an independent world. Since it is considered an autonomous world, the decipherment, interpretation, and judgment are based on the poem itself regardless of the poet, the reader, or reality. This approach is more widely used in poetry. This approach is widely used in poetry. This paper also intends to apply an objective approach in analyzing poetry. Within the scope of poetry, elaborates that the literary work is not only a system of norms but also several strata (layers) of norms. The process of analyzing is directed at understanding the parts of a literary work supporting the whole, and conversely, the whole itself is of the parts. Therefore, to understand its meaning, literary works must be analyzed on the basis of their own structure, detached from the historical background, detached from the author's self and intentions, and their effects on the reader. The only important thing is close reading, that is, a way of reading that is dotted with the opinion that each part of the text should occupy a place within the entire structure so that the hooks make sense. An objective approach, is an approach that orients or focuses attention on the poem itself. Poetry is considered an object of self-sufficiency, an independent world. Since it is considered an autonomous world, the decipherment, interpretation, and judgment are based on the poem itself, regardless of the poet, the reader, or the reality.